Treatment of wastewater using innovative and novel biofilm carriers - Hussein, Hossam Mostafa; Abdelmomen, Mahmoud Mohamed; Taha, Amira Maowed; Nagy, Amira Mohamed (Journal of Degraded and Mining Lands Management, 2025)
This study examined the potential of repurposing agricultural waste as biofilm carriers in Moving Bed Biofilm Reactors (MBBRs) for wastewater treatment. The goal of this experimental research was to reduce the wastewater treatment costs. This research focused on two agricultural by-products: banana stems and corn stalks. These materials were tested as biofilm carriers in a laboratory-scale MBBR setup. Banana stems and corn stalks were prepared to facilitate biofilm formation before being incorporated into the reactor. Results revealed that banana stems achieved reductions of 27% in COD and 32% in BOD, with TSS dropping by 69% during treatment at a filling ratio of 40%. Despite these reductions, the low density of banana stems led to less effective pollutant removal. In contrast, corn stalks demonstrated superior performance, achieving 69% and 83.6% reductions in COD and BOD, respectively, and a 66.7% reduction in TSS at a 40% filling ratio. The higher surface area and better integration of corn stalks with wastewater contributed to more efficient biofilm formation and pollutant degradation than banana stems.